Rejung Bukit Barisan Desa Ulak Agung Kisam dalam Perspektif Sajian Musik - Septiani, Mila Rezeki; Hidayatullah, Fadhilah; Heryanto, A (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Rejung is a regional art of South Sumatra through the spread of Besemah culture. The form of thepackage is a rhyme that uses the Besemah language, developed and equipped with guitaraccompaniment. The problem in this study is the lack of appreciation of the art of rejung to thecommunity in Ulak Agung Kisam Village, Muara Dua Kisam District, South OKU. The purpose ofthis study was to introduce Rejung Art as a local culture in the province of South Sumatra, in UlakAgung Kisam Village, Muara Dua Kisam District, South OKU. The research method used isdescriptive qualitative. Collecting data through observation, interviews, and documentation. Dataanalysis using; data collection, data reduction, data presentation, and conclusions. This researchresulted in the style and technique of presenting Rejung Meringit/Lamentations, Petik Dawi andFate by Orpin Malhadi. The style of mentioning kate-kate Pronunciation of letters in the chantingof the art of rejung, rejung has characteristics and characters on the emphasis of the letters /E/,/I/, and /U/, which can be used at the beginning, middle, suffix, and a mixture of syllables in thepoem , and do the opening in the first remarks and improvisation or creation of rhymes. Thetechnique used is to tell in advance the purpose and theme of the rejung that will be presented,with spontaneity, improvising the rhyme according to the expression of taste, as well as how to sit with the slapstage and using the method with crooked or voice color that has its own character.